Kemas Abdullah Azhari’s Role in Preserving Islamic Scientific Traditions in 20th Century Palembang: A Sustainable Development Perspective - Sodikin; Duski; Adil; Aboubacar Barry; Muhammad Maga Sule; Meriyati; Waliya Purnama Sari (Profetika: Jurnal Studi Islam, 2025)
Objective: This study explores the social contributions of Kemas Abdullah Azhari (1863–1939), a prominent Islamic scholar from Palembang, in preserving Islamic scientific traditions in the 20th century within the framework of the Sustainable Development Goals (SDGs), particularly Goal 4: Quality Education. Theoretical framework: The research is grounded in Max Weber’s theory of social action, particularly the typologies of traditional, charismatic, and bureaucratic authority, to understand the modalities through which Kemas Abdullah Azhari exerted influence in education, religious life, and social conflict resolution. Literature review: The literature review identifies a gap in historiographical sources that address localized Islamic scholarly traditions in Indonesia, particularly those passed on through oral transmission and community memory. Methods: A qualitative narrative method was employed, using document analysis, in-depth interviews with descendants and local figures familiar with the scholar’s legacy, and ethnographic observation of cultural symbols and institutions related to Islamic education in Palembang. The study also incorporated oral traditions and manaqib treatises, which were transmitted intergenerationally in Pedatuan Village. To ensure data reliability, triangulation was applied throughout the research process. Results: Findings reveal that Kemas Abdullah Azhari played a pivotal role in advancing inclusive religious education and creating spaces for the dissemination of Islamic knowledge, aligning with the goals of SDG 4. His contributions ensured the continuity of Islamic scholarship through informal learning and community-based religious instruction, even in the face of colonial constraints and the absence of formal documentation. Implications: This has significant implications for both heritage preservation and contemporary Islamic education strategies. Novelty: The study’s novelty lies in recovering an underexplored dimension of Islamic intellectual history in Sumatra and highlighting the integration of local religious figures in achieving long-term sustainable educational development.